Optimal dosage protocols for mathematical models of synergy of chemo- and immunotherapy - Ledzewicz, Urszula; Schättler, Heinz (Frontiers in Immunology, 2024)
The release of tumor antigens during traditional cancer treatments such as radio-or chemotherapy leads to a stimulation of the immune response which provides synergistic effects these treatments have when combined with immunotherapies. A low-dimensional mathematical model is formulated which, depending on the values of its parameters, encompasses the 3 E's (elimination, equilibrium, escape) of tumor immune system interactions. For the escape situation, optimal control problems are formulated which aim to revert the process to the equilibrium scenario. Some numerical results are included.